Kajian Demokrasi Dan Islam Dalam Pandangan Abdullahi Ahmed An-Na’im - Fahmi Assulthoni (Ulumuna: Jurnal Studi Keilsman, 2018)
Democracy often become ' victims ' of some dissatisfaction among internal impingement Muslims in administering a legitimate Government. Democracy is a Western product may be very weak basic law. He is deemed to have no religious dimension at all, even look does not correspond to what is taught by Islam in the process of implementation of the system of Government. Many more assumptions assumptions are less responsive and based on the basic law. This is confirmed by the figures of moderate Muslims who argued that Islam and democracy is indeed a unity that can not be separated. Both have ties dahir and inner when adopted as a central system running. Democracy is Islam, and Islam is democracy.